A Clinico-Epidemiological Study of Ocular Trauma in Indian University Students - K. Singh, Prashant Bhushan, Rajendra P. Maurya, Kundan Sinha, Prithvi R. Sen, Virendra P. Singh Mahend (Pakistan Journal of Ophthalmology, 2018)
Purpose: To observe the pattern, severity and outcome of ocular injuries and to identify the etiological factors responsible for ocular trauma among University students. Material and Methods: This prospective interventional study was conducted in university students health care complex and department of ophthalmology, Institute of Medical Sciences, Banaras Hindu University, Varanasi from September 2009 to August 2011. One hundred and sixty six university students with eye injuries attending as outpatient or emergency patient were thoroughly examined as per standard clinical procedures to identify the cause, type, extent and severity of injuries and impact on vision. The follow up period was six months. Results: Out of the 166 patients, 117 (70.48%) were male while 49 (29.52%) were females. Patients were aged between 16 and 45 years. 67.47% were delegacy students while 32.53% were hostellers. Mechanical injuries accounted for 70.48%, while rest were chemical (11.44%), thermal (9.04%) and radiational injuries (9.04%). Most of the injuries occurred at workplace (25.90%) or on the road (25.30%), hostel/residence (21.69%) and during play and sports (19.28%). 79.29% students suffered accidental injuries and rest 27.71% had assault related injuries. The assault related injuries were more common amongst male students (21.69%). 56.02% of mechanical injuries were caused by blunt objects and rest 14.46% were due to sharp objects. Commonest type was periocular and lid injury (50%), followed by globe injury (44.58%) and orbital injury (5.42%). Left eye was affected in 42.77%, right eye in 34.94% while in 22.29% cases both the eyes were involved. 23.49% student suffered from severe injury, 36.49% had moderate while 40.96% sustained minor injuries. There was bimodal seasonal distribution with first spike during spring and second during rainy season. 73.49% of the injured patients were managed by conservative treatment while rest underwent surgical procedures. The final visual acuity was 6/18 or better in 60.24% patients between 6/18 to 3/60 in 24.11% and 3/60 or less in 12.65%. Assessment was not possible in 3.01% cases. Conclusion: This study highlights epidemiology of ocular trauma in university students. Health education and preventive strategies should be focussed specially during workshop, laboratory work, in play ground and while driving.